REFLEKSI DINAMIKA REFORMASI ORGANISASI BIROKRASI INDONESIA DI MASA DEPAN - Tommy F. Lolowang (Jurnal Manajemen Kepegawaian, 2008)
This writing take theme/topic with complexity about problem which classic, fundamental, but regular actual. Be said to be classic because bureaucracy organization problem was worked through since Antic Greek era Plato and Aristoteles. Hereinafter referred to as fundamental because bureaucracy problem constitute basic problem and its formative aim touches various dimension and individual life joint and society. Called by actual because in the context current condition bureaucracy problem always emerges, not only circumscribed as discourse but also as debate target, well political and also non political. For over clarifies and secure dynamics and organisational development aim Indonesian bureaucracy at future the better, worth considering steps covers: Changing Bureaucracy Culture, Pancasila Revitality as Core Philosophy Bureaucracy, Implementation Bureaucracy Ethics consistently, and Secures Bureaucracy Neutrality. Keywords: Dynamics and Organisational Development, Bureaucracy, Pancasila, Culture, Ethics, Neutrality